Managing Southern Chinch Bug in Warm Season Turfgrasses - Eileen A. Buss; Brianna Whitman; Adam G. Dale (EDIS)
Southern chinch bug, Blissus isularis Barber, is the most damaging insect pest of St. Augustinegrass in the United States. St. Augustinegrass is the most common turfgrass used in Florida. The ubiquity of this single turfgrass species makes southern chinch bug an economically important pest in the state. In fact, chinch bugs cost Florida homeowners and professionals millions of dollars every year. This 7-page fact sheet written by Eileen A. Buss, Brianna M. Whitman, and Adam G. Dale and published by the UF/IFAS Department of Entomology and Nematology describes the biology of the pest and the damage it causes and lists ways to scout and monitor for chinch bugs and some strategies for control of the pest. https://edis.ifas.ufl.edu/lh036